The Role of the Judicial Presumption in Criminal Proof According to the Jordanian Code of Criminal Procedure - Haddad, Mohannad .W. Al (Journal of Posthumanism, 2024)
The judicial presumption is of great importance in criminal proof, because the truth cannot be reached without it. And it has a great value in proof in terms of strengthening other evidence on which the judge relies to form his emotional conviction. Rather, it is often the basis on which the judge balances the different evidence and evaluates the evidence before him in order to reach a fair judgment decision. Since the judicial presumption is not exclusively mentioned in the penal legislation, it is considered indirect evidence, but it is sufficient to establish the judge's conviction about the incident presented to him. Therefore, it was necessary to address this subject and shed light on all its aspects to determine its nature and to clarify its role in the criminal proof.